Applying capability maturity model to curriculum design : a case study at private institution of higher learning in Malaysia. - Thong, C. L.; Jusoh, Yusmadi Yah; A., Rusli; A., Nor Hayati (2012)
Capability Maturity Model (CMM) was applied as a process improvement model not only in software industry but also in education sector. In this study, Capability Maturity Model is applied to investigate whether process improvement can be generated in designing curriculum for Institution of Higher Learning. Therefore, a model which contains a set of key process areas and best practices is constructed and presented based on the literature study, and a case study is carried out in a private Institution of Higher Learning in Malaysia. It is discovered that the model offers a means for institution to self-assess the curriculum design process and may put forward guidance in designing a sound curriculum. The model also may help the institution to determine their maturity level; whether the process has obtained any maturity level and subsequently they are guided to complete the process before moving to next level. In addition, the results may also help the institution to be informed of future improvement process